2022
DOI: 10.1038/s41598-022-15091-z
|View full text |Cite
|
Sign up to set email alerts
|

Milk microbiomes of three great ape species vary among host species and over time

Abstract: In mammalian neonates, milk consumption provides nutrients, growth factors, immune molecules, and microbes. Milk microbiomes are increasingly recognized for their roles in seeding infant gut microbiomes and priming immune development. However, milk microbiome variation within and among individuals remains under investigation. We used 16S rRNA gene sequencing to investigate factors shaping milk microbiomes in three captive great ape species: Gorilla gorilla gorilla (individuals, N = 4; samples, n = 29), Pongo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…6 b), indicating that B 12 supplementation significantly enhanced the interaction relationship between intestinal microbiota. Interestingly, the detected network hub (OTU0155) and module hub (OTU0026), as well as most of the connectors, were rare taxa, suggesting that less abundant bacteria play regulator roles in the microbial ecological network [ 83 ]. Taken together, B 12 supplementation increased the complexity of the gut microbial ecological network and improved the interactions between gut microbes.…”
Section: Resultsmentioning
confidence: 99%
“…6 b), indicating that B 12 supplementation significantly enhanced the interaction relationship between intestinal microbiota. Interestingly, the detected network hub (OTU0155) and module hub (OTU0026), as well as most of the connectors, were rare taxa, suggesting that less abundant bacteria play regulator roles in the microbial ecological network [ 83 ]. Taken together, B 12 supplementation increased the complexity of the gut microbial ecological network and improved the interactions between gut microbes.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed similar microbiomes at early and mature lactation stages, suggesting similar ecoevolutionary processes are controlling milk microbiome composition across lactation. Previous studies have found variation in milk microbiomes across lactation in some species, namely primates ( 5 , 12 , 27 ), suggesting that temporal variation in milk microbiomes occurs in some species and may best be detected with greater longitudinal sampling resolution within specific species or animal groups. Our study encompasses hosts across the mammalian tree and lends itself to broad comparisons across lactation, in which we found that factors such as evolutionary history, external and internal environments, and stochasticity shape the mammalian milk microbiome throughout lactation.…”
Section: Discussionmentioning
confidence: 97%
“…Host-associated microbial communities are unique in that these filters are acting at both the host level and the host body site level, such that the environment of the host affects the regional pool of microbial species (e.g., in a forest) and the environment of the host’s body site for which the microbes will colonize acts as a secondary ecological filter (e.g., gut pH). For instance, we have previously shown that where an individual lives influences their milk microbiome ( 27 ) and that milk nutrient content (milk fat, milk sugar, and milk protein) is related to species differences in milk microbiome composition in primates ( 5 ).…”
mentioning
confidence: 99%
“…In our own research, we have been able to extract and sequence bacterial DNA from 86% of milk samples (163/190 samples) from nine species on anthropoid primates, including humans (Muletz-Wolz et al 2019), and from 86% of milk samples (107/127) from 47 species of placental mammals from all four super orders (Keady et al 2023). Although there are remaining technical challenges in the detection and purification of milk microbial communities, there is a burgeoning literature supporting the existence of consistent, functional microbial communities in mammal milk that vary with host diet, phylogeny, and geographic location (Muletz-Wolz et al 2019, Petrullo et al 2019, Ge et al 2021, Bornbusch et al 2022, Keady et al 2023.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we will briefly outline the evidence for a milk microbiome in a wide range of placental mammals. Compelling evidence indicates that milk hosts viral (Pitino et al 2021), archaeal (Togo et al 2019, Keady et al 2023), bacterial (Muletz-Wolz et al 2019, Bornbusch et al 2022) and fungal species (Boix-Amorós et al 2019). However, the vast majority of research focuses on bacterial communities, and thus the primary focus of our review will be on bacterial milk microbiomes, unless otherwise noted.…”
Section: Introductionmentioning
confidence: 99%